Heart failure and treatment with Sodium-glucose Co-transporter Inhibitor (SGLT2): dapagliflozin and its effects on the cardiac system - Reckel, Leandro de Oliveira (2024)
This article thoroughly examines the effectiveness of treatment with dapagliflozin, a sodium-glucose co-transporter inhibitor, in the context of heart failure. The primary focus of this analysis lies in evaluating patients' clinical condition, the diagnostic procedures employed, and the various medications used as part of the treatment regimen. The objective of this investigation is based on a meticulous analysis of relevant scientific articles. Classified as documentary research within the field of Applied Linguistics, this study draws upon research covering classification, pathophysiology, clinical presentation, diagnosis, pharmacological treatment, and the role of SGLT2 inhibitors in heart failure as its primary theoretical framework. The findings indicate dapagliflozin's efficacy in reducing the heart's ejection fraction, regardless of the presence of diabetes. However, it emphasizes the importance of a comprehensive medical assessment before initiating the use of this medication, highlighting the need for caution and appropriate professional supervision.